Independent community libraries an exploratory study - Oida, Archimedes P.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Government creation of public libraries for the people have been lacking in the Philippines, however one little studied way that this is addressed is by communities forming libraries of their own independent of the state. A study of this is thus warranted in order to more fully understand and take advantage of this phenomenon.
Four libraries, ABAKADA Children's Community Library, KADAMAY Bulilit Learning Center, Reading Club 2000 and Antipolo Kiwanis Community Library were selected for said purposes. The libraries were observed, described and interviews with the librarians or library managers were conducted to shed light on the history and operations of the four libraries, basing the interview schedule on University of California, Berkeley's library service model.
From the data gathered it was found that library conceptualization and creation was based on the particular agency of NGOs or individuals and not through any broader movement, and thus reflect their agenda. There is lack of rigorous reference work, selection, and weeding. Most of the acquisitions are from donations, and because of the volume and limited space, many donate extra material to other libraries particularly more destitute school libraries. Indeed in general, the libraries focus on the education of the children and the youth, especially the disenfranchised. Finally, all four only have untrained para-librarians to man their libraries.
Despite their flaws the libraries provide an important service to the communities that they are part of, providing a supplement to the public library system. It is thus beneficial not only to encourage the formation of more of such, but to support the improvement of these libraries.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman Archives and Records Depository; Libraries and community -- Philippines -- Manila Metropolitan Area